Selling to Strategic Consumers When Product Value Is Uncertain: The Value of Matching Supply and Demand - Swinney, Robert (Management Science, 2011)
We address the value of quick response production practices when selling to a forward-looking consumer population with uncertain, heterogeneous valuations for a product. Consumers have the option of purchasing the product early, before its value has been learned, or delaying the purchase decision until a time at which valuation uncertainty has been resolved. Whereas individual consumer valuations are uncertain ex ante, the market size is uncertain to the firm. The firm may either commit to a single production run at a low unit cost prior to learning demand, or commit to a quick response strategy that allows additional production after learning additional demand information. We find that the value of quick response is generally lower with strategic (forward-looking) customers than with nonstrategic (myopic) customers in this setting. Indeed, it is possible for a quick response strategy to decrease the profit of the firm, though whether this occurs depends on various characteristics of the market; specifically, we identify conditions under which quick response increases profit (when prices are increasing, when dissatisfied consumers can return the product at a cost to the firm) and conditions under which quick response may decrease profit (when prices are constant or when consumer returns are not allowed). This paper was accepted by Martin Lariviere, operations and supply chain management.